2013
DOI: 10.2298/vsp110429016p
|View full text |Cite
|
Sign up to set email alerts
|

Impaired endothelial function in lone atrial fibrillation

Abstract: Our findings confirm that sustained AF is associated with systemic endothelial dysfunction even in relatively young patients with no cardiovascular disorders or risk factors. AF is an independent contributor to lower FMD and a prolonged arrhythmia duration may confer the risk for more profound endothelial damage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 37 publications
3
13
0
1
Order By: Relevance
“…Despite evidence of inflammatory atrial lesions [ 16 ] and increased levels of various biomarkers in lone AF [ 17 ], there is no unequivocal link between inflammation, oxidative burden, AF, and vascular disease. In the present study, we have demonstrated higher CRP levels in AF patients compared to healthy controls, which is in line with our previous findings of impaired endothelial function and increased CRP concentrations in subjects with persistent lone AF compared to healthy individuals [ 18 ]. Similarly, increased levels of CRP [ 13 ] and other mediators of inflammation [ 19 ] have been reported in other studies of lone AF patients, with a stepwise CRP elevation associated with increased AF burden [ 13 ].…”
Section: Discussionsupporting
confidence: 93%
“…Despite evidence of inflammatory atrial lesions [ 16 ] and increased levels of various biomarkers in lone AF [ 17 ], there is no unequivocal link between inflammation, oxidative burden, AF, and vascular disease. In the present study, we have demonstrated higher CRP levels in AF patients compared to healthy controls, which is in line with our previous findings of impaired endothelial function and increased CRP concentrations in subjects with persistent lone AF compared to healthy individuals [ 18 ]. Similarly, increased levels of CRP [ 13 ] and other mediators of inflammation [ 19 ] have been reported in other studies of lone AF patients, with a stepwise CRP elevation associated with increased AF burden [ 13 ].…”
Section: Discussionsupporting
confidence: 93%
“…There is a constant, gradual, and consistent relationship between blood pressure and stroke risk. As blood pressure increases, the risk of stroke increases, even if it is not in the hypertensive range (10). In our study, hypertension was the most common comorbid disease, like other studies.…”
Section: Discussionsupporting
confidence: 78%
“…Although heterogeneity in T2DM‐related risk in relation to background left ventricular function has not been explored in AF, it has been demonstrated in HF, where the association between T2DM and mortality or hospitalisation for HF was greater in magnitude in individuals with LVEF ≥40% than in patients with LVEF <40% . Available data suggest that both AF and HFpEF may be considered as systemic disorders that commonly share an association with increased markers of inflammation, fibrosis, and systemic and microvascular endothelial dysfunction . The presence of T2DM may aggravate these pathological processes leading to the more prominent left ventricular diastolic dysfunction and hypertrophy and more pronounced left atrial remodelling, and in turn, to the greater propensity to manifest HFpEF.…”
Section: Discussionmentioning
confidence: 99%
“…40,41 Available data suggest that both AF and HFpEF may be considered as systemic disorders that commonly share an association with increased markers of inflammation, fibrosis, and systemic and microvascular endothelial dysfunction. 39,42,43 The presence of T2DM may aggravate these pathological processes leading to the more prominent preceding HF occurrence at follow-up. ACS, acute coronary syndrome; AF, atrial fibrillation; HFmrEF, heart failure with mid-range ejection fraction; HFpEF, heart failure with preserved ejection fraction; HFrEF, heart failure with reduced ejection fraction; T2DM, type 2 diabetes mellitus.…”
Section: The Association Between Type 2 Diabetes and Outcomesmentioning
confidence: 99%